Thrombolysis in acute ischemic stroke is associated with lower long-term hospital bed day use: A nationwide propensity score-matched follow-up study. Issue 8 (October 2016) - Terkelsen, Thorkild; Schmitz, Marie Louise; Simonsen, Claus Z; Hundborg, Heidi H; Christensen, Hanne K; Gyllenborg, Jesper; Sandal, Birgitte F; Iversen, Helle K; Madsen, Charlotte; Rasmussen, Mary-Jette; Vestergaard, Karsten; Andersen, Grethe; et al.
Background: Thrombolysis with intravenous recombinant tissue-type plasminogen activator improves functional outcome in acute ischemic stroke. Few studies have investigated the effects of thrombolysis in a real-world setting. We evaluated the impact of thrombolysis on long-term hospital bed day use and the risk of readmission due to stroke-related complications. Methods: We conducted a register-based nationwide propensity score-matched follow-up study among ischemic stroke patients in Denmark (2004–2011). Thrombolysed patients were propensity-score matched with non-thrombolysed acute ischemic stroke patients admitted to stroke centers not yet offering thrombolysis in 2004–2006. The outcomes were length of the stroke admission, total all-cause hospital bed day use during the first year after the stroke, and the long-term risk of readmissions. Thrombolysed and non-thrombolysed patients were compared using multivariable log-linear regression and Cox regression. Results: We identified 1095 thrombolysed and 1095 propensity score matched eligible but non-thrombolysed acute ischemic stroke patients. The median length of the stroke admission was 9 days in the thrombolysed group and 13 days in the non-thrombolysed group (adjusted geometric mean ratio, 0.88; 95% CI: 0.78–1.00). The median all-cause hospital bed day use within the first year was 12 days in the thrombolysed group and 19 days in the non-thrombolysed group (adjusted geometric mean ratio, 0.82; 95% CI: 0.73–0.92). There was no significant difference in the overall risk of readmission (adjusted hazard ratio, 0.91; 95% CI: 0.79–1.04); however, thrombolysis was associated with reduced risk of pneumonia (adjusted hazard ratio, 0.59; 95% CI: 0.35–0.97). Conclusions: Thrombolysis in ischemic stroke was associated with lower long-term hospital bed day use and decreased risk of readmission due to pneumonia.